Analysis of Guided Inquiry Learning Devices to Improve Students' Creative Thinking Skills - Maria Gradiana Mau; Wasis Wasis; Tjipto Prastowo (Indonesia Emerging Literacy Education, 2023)
Objective: This study aims to produce a science learning tool validity using the guided inquiry model to improve the creative thinking skills of 8th-grade students. This research is descriptive and quantitative. Method: The research method is developed with Four-D (4D) stages. This research will validate the learning tool consisting of a syllabus, lesson plans, student worksheets, teaching materials, and student creative thinking ability test sheets. Moreover, the object of this study is the learning device's validity level. The data analysis technique was qualitative and descriptive based on assessing the three validators. Results: The results of the three validators concluded that the syllabus has an average score of 3.55 with valid criteria, and the lesson plan with an average score of 3.70. with valid criteria. Student worksheets have an average score of 3.49 with good standards, student teaching materials have an average score of 3.49 with very proper measures, and student teaching materials have an average score of 3.67 with valid criteria. The student's creative thinking ability test sheet has an average score of 3.64 with a correct category. Thus, the learning tools developed can be used in the learning process to improve students' creative thinking skills. Novelty: The use of guided inquiry learning tools is an effective tool in the learning process to improve students' creative thinking skills with the hope that this learning experience will be applied in dealing with various problems in everyday life.